Peace and its discontents : essays on Palestine in the Middle East peace process - Said, Edward W. (Vintage Books, 1996)
In works such as "Culture and Imperialism," Said has compelled us to question our culture's most privileged myths. Now with this impassioned and incisive book, our foremost Palestinian-American intellectual challenges the official version of the Middle East "peace process." "He challenges and stimulates our thinking in every area."-- "Washington Post Book World"